Sphere of subsurface use: relevance of institutional and integration changes - S. V. Lisov; V. I. Lisov (Известия высших учебных заведений: Геология и разведка, 2016)
The features of the institutional regulation of the subsoil use sphere which are subjected to be taken into account in case of the enhancement of the legislation on the strategic planning and industrial policy, are formulated. The task of the ensuring the balanced functioning of the education, sciences and productions in the mineral and raw complex is set. The basic principles of the integration of the production, scientific and technical and educational organizations are offered.